Heavy quarkonium spectral function in the spinning black hole background - Zhou-Run Zhu; Manman Sun; Rui Zhou; Zhuang Ma; Jinzhong Han (European Physical Journal C: Particles and Fields)
Abstract In this paper, we study the dissociation of heavy quarkonium in the spinning black hole background. Specifically, we analyze the spectral function of charmonium and bottomonium in the spinning black hole background and examine how the angular momentum affects the dissociation of $$J/\Psi $$ J / Ψ and $$\Upsilon (1S)$$ Υ ( 1 S ) . From the results, we find that the angular momentum and temperature decreases the peak height and expands the peak width of the spectral function, thereby enhancing the dissociation of heavy vector mesons. Moreover, the angular momentum has a stronger dissociation effect in the transverse orientation, revealing the directional influence of angular momentum.